2021
DOI: 10.1126/science.abg5433
|View full text |Cite
|
Sign up to set email alerts
|

The global threat from plastic pollution

Abstract: Plastic pollution accumulating in an area of the environment is considered “poorly reversible” if natural mineralization processes occurring there are slow and engineered remediation solutions are improbable. Should negative outcomes in these areas arise as a consequence of plastic pollution, they will be practically irreversible. Potential impacts from poorly reversible plastic pollution include changes to carbon and nutrient cycles; habitat changes within soils, sediments, and aquatic ecosystems; co-occurrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
644
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,428 publications
(654 citation statements)
references
References 64 publications
1
644
0
9
Order By: Relevance
“…Both of these options have significant negative environmental effects. Discarded plastics are a major global concern with plastic waste, both macro and micro, found in every environment globally [57,61,62]. The very slow rate of degradation means that plastic waste will remain present for unacceptably long periods of time.…”
Section: Backsheet Polymersmentioning
confidence: 99%
“…Both of these options have significant negative environmental effects. Discarded plastics are a major global concern with plastic waste, both macro and micro, found in every environment globally [57,61,62]. The very slow rate of degradation means that plastic waste will remain present for unacceptably long periods of time.…”
Section: Backsheet Polymersmentioning
confidence: 99%
“…However, to date, no certification scheme for 'AD-able' material exists, and even some of the most biodegradable EN 13432 materials (industrial composting certification scheme) were shown not to meet the physical contaminant criteria of the PAS 110 specification, the national quality standard for the digestate market in the UK [51]. This is alarming, especially in light of microplastic and plasticiser accumulation reported in agricultural soils [67,68]. Soil biodiversity and, consequently, soil fertility could be severely undermined with increasing levels of plastic pollution [68].…”
Section: Legislative Economic and Environmental Challengesmentioning
confidence: 99%
“…This is alarming, especially in light of microplastic and plasticiser accumulation reported in agricultural soils [67,68]. Soil biodiversity and, consequently, soil fertility could be severely undermined with increasing levels of plastic pollution [68].…”
Section: Legislative Economic and Environmental Challengesmentioning
confidence: 99%
“…Noteworthy, the situation has substantially worsened as a consequence of the COVID-19 outbreak [30,31] . Land dumped plastic waste is transported by the river network [32] with an annual estimated amount of 1.2-2.4 million tons in 2016 [33] . Under business-as-usual scenarios, these emission rates could be doubled by 2025 [34] .…”
Section: Broadening the Scope Of Water Contaminants: Micro-and Nano-plasticsmentioning
confidence: 99%